Associations of eHealth Literacy with Diabetes Self-Efficacy and Glycemic Parameters in Individuals with Type 2 Diabetes and Prediabetes: A Cross-Sectional Study - Kemal Ozan Lüle; Sümeyye Akçoban; Aylin Berk; Neşe Ataman Bor; Soner Berşe (Healthcare, 2026)
Background/Objectives: eHealth literacy may support diabetes self-management, but its relationships with diabetes self-efficacy and glycemic outcomes remain unclear. This study examined these associations among adults with type 2 diabetes mellitus (T2DM) and prediabetes and evaluated whether the observed association between eHealth literacy and HbA1c was statistically consistent with an indirect association through diabetes self-efficacy. Methods: This cross-sectional study included 273 adults with T2DM or prediabetes attending an internal medicine outpatient clinic in Türkiye. Data were collected using the eHealth Literacy Scale, Diabetes Self-Efficacy Scale, and a clinical characteristics form; HbA1c and fasting plasma glucose values were obtained from medical records. Correlation, regression, and bootstrapped statistical indirect-association analyses were performed. Results: eHealth literacy was positively associated with diabetes self-efficacy (rho = 0.310, p < 0.001; β = 0.345, p < 0.001). Its association with HbA1c was non-significant after adjustment. Among participants with T2DM, higher self-efficacy was associated with lower HbA1c (β = −0.224, p = 0.026), whereas longer disease duration was associated with higher HbA1c (β = 0.201, p = 0.023). A significant statistical indirect association between eHealth literacy and HbA1c through diabetes self-efficacy was observed. Conclusions: This study provides correlational evidence that eHealth literacy is associated with diabetes self-efficacy and that this relationship may partly account for the observed statistical association between eHealth literacy and glycemic control. The cross-sectional design precludes conclusions regarding temporal or causal mediation.